Impact of "Made in China 2025" industrial strategy on firms' green innovation: A quasi-natural experiment - Asif Razzaq; Dina Azhgaliyeva; Dil Bahadur Rahut (Asian Development Bank Institute (ADBI), 2024)
Industrial policies are considered pivotal for fostering green innovation and elevating enterprise development. They offer vital guidance for expediting the evolution of innovation systems, enhancing enterprise green competitiveness, and catalyzing the emergence of new sources of enterprise growth. Given this, we investigate the impact of the "Made in China 2025" strategy, implemented in 2015, on enterprises' green innovation using a double-difference model to analyze this quasi-natural experiment. Our findings reveal that the "Made in China 2025" industrial policy intervention significantly enhances green innovation among enterprises. These results remain consistent across various robustness checks, including parallel trends, placebo tests, and additional robustness measures. The study uncovers that the impact of this policy varies by location, sector, and the degree of pollution among enterprises, with those in the eastern regions and those with lower pollution levels experiencing more pronounced positive effects. The results indicate that alleviating corporate financing constraints, advancing digital transformation, and improving regional marketization are core transmission channels through which the "Made in China 2025" policy influences firms' green innovation performance.
Keywords: L52; O25; L62; l63; 330; Made in China 2025; industrial policy; green innovation; financing constraints; digital transformation; regional marketization level